Traumatic cardiac arrest. (January 2015) - Smith, Jason E; Rickard, Annette; Wise, David
Traumatic cardiac arrest is known to have a poor outcome, and some authors have stated that attempted resuscitation from traumatic cardiac arrest is futile. However, advances in damage control resuscitation and understanding of the differences in pathophysiology of traumatic cardiac arrest compared to medical cardiac arrest have led to unexpected survivors. Recently published data have suggested that outcome from traumatic cardiac arrest is no worse than that for medical causes of cardiac arrest, and in some groups may be better. This review highlights key areas of difference between traumatic cardiac arrest and medical cardiac arrest, and outlines a strategy for the management of patients in traumatic cardiac arrest. Standard Advanced Life Support algorithms should not be used for patients in traumatic cardiac arrest.